2018
DOI: 10.1155/2018/4632081
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Diacetate Esters of Macular Carotenoids: Effect of Supplementation on Macular Pigment

Abstract: The accumulation of the carotenoids lutein, zeaxanthin, and mesozeaxanthin in the center of the human retina, and known as the macula lutea or macular pigment, is believed to protect the retina from age-related macular degeneration. Since the macular pigment is of dietary origin, supplements containing the relevant carotenoids are readily available. In this study, we compared the changes in macular pigment over a 24-week supplementation period for two groups of 24 subjects each assigned to either of two supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In the present study, the serum response to Zd and MZd (Group 4, solubilised acetate-esterified XC) was significantly greater compared to the formulations containing free carotenoids. However, it was striking to see that the serum response to Ld remained similar to that of free L. This, however, is consistent with a previous clinical trial performed by Landrum et al, which reported that serum response to Ld was slightly higher but not statistically different when compared to the group supplemented with free L provided as microcrystals in oil [ 28 ]. Interestingly, the results of a study in hens conducted by our group to assess the bioavailability of XC diacetates are similar to the present work, as Zd and MZd exhibited a greater capability to increase the deposition of Z and MZ in egg yolk than the free form of these carotenoids [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, the serum response to Zd and MZd (Group 4, solubilised acetate-esterified XC) was significantly greater compared to the formulations containing free carotenoids. However, it was striking to see that the serum response to Ld remained similar to that of free L. This, however, is consistent with a previous clinical trial performed by Landrum et al, which reported that serum response to Ld was slightly higher but not statistically different when compared to the group supplemented with free L provided as microcrystals in oil [ 28 ]. Interestingly, the results of a study in hens conducted by our group to assess the bioavailability of XC diacetates are similar to the present work, as Zd and MZd exhibited a greater capability to increase the deposition of Z and MZ in egg yolk than the free form of these carotenoids [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the digestive system, this soluble state facilitates the incorporation of XCs into micromicelles, which are spherical aggregates of lipid molecules in the presence of amphiphilic compounds known as surfactants [ 24 , 26 ]. This formulation has been previously tested [ 27 , 28 , 29 ] in clinical trials and compared to crystallised formulations (free lutein).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 3 RCTs ( 9 , 34 , 48 ) and 2 non-RCTs ( 55 , 64 ) compared a supplement with meso-zeaxanthin to placebo or another supplement without meso-zeaxanthin. The interventions in these trials were very heterogenous, and the results of these trials were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Bone et al ( 64 ) compared a daily liquid supplement with 15 mg lutein, 3 mg zeaxanthin, and 10 mg of meso-zeaxanthin to a daily gel capsule supplement with 10 mg lutein and 2 mg zeaxanthin and reported a statistically significant increase in MPOD among participants who received the liquid supplement compared with the participants who received the gel capsule supplement. Bone et al ( 55 ) compared a daily supplement with 9.1 mg of lutein, 9.1 mg of zeaxanthin, and 1.8 mg of meso-zeaxanthin to a daily supplement with 19 mg of lutein and 1 mg of zeaxanthin. There was a significant change in MPOD among older adults, but not among younger adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation